Digital Marketing and Social Media Marketing Trends in Kosovo - Luan Jusufi; Sokol Xhafa (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
With the ever-increasing development in information and communication technology and the spread of the internet into personal computers and mobile devices, the promotion of products has become an essential component in the new digital age, mostly thanks to digital marketing.  Every day, companies increasingly share information on the internet to connect with customers through social media, digital advertising, email marketing, and online brochures, enabling the transition from traditional marketing to digital marketing.  Through digital marketing, companies promote their products and services using social networks and inform their customers through personal messages about the characteristics of the products they offer on the market, which directly affect and increase sales. Following global tendencies and practices, Kosovo companies increasingly use digital marketing to communicate with customers and promote products and services primarily through social media. Nowadays, regardless of whether a company produces and sells high-quality products and services, promotion through digital marketing is one of the most important things a business needs to do. Kosovar companies follow this trend of promoting products and services through digital marketing, mainly social media marketing. This paper discusses the transition from traditional marketing to digital marketing in Kosovo. We examine the trend of using digital marketing, mainly social media marketing by Kosovar citizens and businesses, based on the results of surveys conducted by the Regional Cooperation Council 2022 edition of the Balkan Barometer for citizen and business perception in Western Balkan Countries.  The goal of this paper is not only to determine the growing trend of digital marketing and social media marketing but also to evaluate their impact on increasing sales of products and services for Kosovar businesses compared to other Western Balkan countries.
Keywords: M30; 330; Digital Marketing; Social Media Marketing; trend in advertising in social media; Kosovo; Western Balkans